2020
DOI: 10.1002/jso.25853
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for sentinel lymph node mapping in gynecologic malignancies

Abstract: Background and Objectives Only a few studies have reported the learning curve for sentinel lymph node (SLN) detection in gynecologic malignancies. We investigated the learning curve for SLN detection during robot‐assisted laparoscopic surgery for endometrial and cervical carcinomas. Methods This retrospective analysis included patients with stage IA to IIA1 cervical cancer or stage I to III endometrial cancer who underwent SLN mapping using indocyanine green during robot‐assisted laparoscopic surgery performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In breast cancer, a minimum of 20 SLN procedures were required to be proficient in SLN algorithm. 29 Kim et al 30 Several studies have revealed that SLN mapping could help to detect metastases beyond the region of routine pelvic lymphadenectomy (ie, unusual localizations). 15,31 These unusual localizations include the para-aortic region, common iliac region, parametrial region and presarcal region.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, a minimum of 20 SLN procedures were required to be proficient in SLN algorithm. 29 Kim et al 30 Several studies have revealed that SLN mapping could help to detect metastases beyond the region of routine pelvic lymphadenectomy (ie, unusual localizations). 15,31 These unusual localizations include the para-aortic region, common iliac region, parametrial region and presarcal region.…”
Section: Discussionmentioning
confidence: 99%
“… 45 This is in line with the recently reported learning curve of at least 27 cases for SLN mapping with ICG. 46 A learning curve effect is further substantiated by Balaya et al, who showed that centers with less than five patients per year had significantly lower bilateral mapping rates than the so‐called “high skilled centers” (≥5 patients per year). 43 The learning curve of the SLN procedure—irrespective of the tracer used—may have contributed to the variation in reported detection rates of 99m Tc with blue dye.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, it is important to assess the learning curve, considered an independent factor that can influence the quality of the technique. This has been estimated at a total of 20-30 surgeries, improving with the accumulation of cases per surgeon, although it seems to be independent of experience in minimally invasive surgery [19] . In our study the learning curve occurred in 10 surgeries, since from patient number 11 onwards bilateral DR improved considerably.…”
Section: Discussionmentioning
confidence: 99%